Acute promyelocytic leukemia with FIP1L1::RARA fusion gene: The clinical utility of transcriptome sequencing and bioinformatic analyses - Liu, Guanghua; Long, Jiangwen; Chen, Yuyu; Li, Lingqian; Huan, Xisha; Long, Panpan (Frontiers in Oncology, 2023)
Background Acute promyelocytic leukemia (APL) is typically characterized by the the presence of coagulopathy and PML-RARA fusion gene.The FIP1L1-RARA has been reported as a novel fusion gene, studies on its pathogenesis are limited. Objectives A FIP1L1-RARA fusion in a child finally diagnosed as APL was reported. RNA sequencing (RNA-seq) of six patients (three cases of acute lymphoblastic leukemia(ALL), myelodysplastic syndrome(MDS), acute megakaryoblastic leukemia (M7) and APL with FIP1L1-RARA) were performed. Methods Transcriptome analysis of six patients were performed by RNA-seq. The heat map was used for showing the RNA expression profile, the volcano plot for identifying differential expression genes (DEGs) and Orthology-Based Annotation System (KOBAS) online biological information database for KEGG pathway enrichment analysis. Results Obvious difference between APL with FIP1L1-RARA and hematologic malignancies were identfied. 1060 common differentially expressed genes (co-DEGs) were detected between APL with FIP1L1-RARA vs ALL and APL with FIP1L1-RARA vs myeloid neoplasms (MDS, M7), the up-regulated genes were mainly mapped into platelet activation, cancer, AMPK signaling pathway, PI3K-Akt signaling pathway and MAPK signaling pathway. The down-regulated genes were signifcantly associated with TNF signaling pathway, Rap1 signaling pathway, Age-RAGE signaling pathway and apoptosis. Conclusion A FIP1L1-RARA fusion in a child finnally diagnosed as APL was reported. RNA-seq maybe a new diagnostic method when RARA rearrangements are failed to be identified by conventional methods. In analysis of co-DEGs between case vs ALL and case vs myeloid neoplasms, the up-regulated and down-regulated genes were enriched in different signaling pathways. Further experimental studies are needed to identify pathogenesis and treatment for APL with FIP1L1-RARA.